Gendered pathways to educational aspirations: The role of academic self-concept, school burnout, achievement and interest in mathematics and reading. (December 2016) - Korhonen, Johan; Tapola, Anna; Linnanmäki, Karin; Aunio, Pirjo
Abstract: The aim of this study was to examine lower secondary school students' ( N = 1152) pathways to educational aspirations. The study used multi-group structural equation modelling to investigate the predictions of academic self-concept, school burnout, achievement, and interest in mathematics and reading, in relation to educational aspirations for boys and girls. While certain factors were influential for students' academic aspirations irrespective of gender, some interesting differences also emerged. Academic self-concept and interest in reading predicted educational aspirations for both groups. However, gendered pathways emerged in how achievement and interest in mathematics predicted educational aspirations. Interest in mathematics predicted girls' educational aspirations, whereas mathematics achievement was a significant predictor for boys. School burnout had negative indirect effects through interest in reading and mathematics in both groups, but for girls, there was also a direct positive effect on educational aspirations. Highlights: Gendered pathways emerged from mathematics measures to aspirations. Reading achievement predicted aspirations through interest. Academic self-concept predicted aspirations for both genders. School burnout had negative indirect effects on aspirations through interest. School burnout also had a direct positive effect on girls' educational aspirations.